The consequence of substrates of large-scale rigidity on actin network tension in adherent cells. Issue 13 (3rd October 2019) - Manifacier, Ian; Beussman, Kevin M.; Han, Sangyoon J.; Sniadecki, Nathan J.; About, Imad; Milan, Jean-Louis
Abstract: There is compelling evidence that substrate stiffness affects cell adhesion as well as cytoskeleton organization and contractile activity. This work was designed to study the cytoskeletal contractile activity of single cells plated on micropost substrates of different stiffness using a numerical model simulating the intracellular tension of individual cells. We allowed cells to adhere onto micropost substrates of various rigidities and used experimental traction force data to infer cell contractility using a numerical model. The model shows that higher substrate stiffness leads to an increase in intracellular tension. The strength of this model is its ability to calculate the mechanical state of each cell in accordance to its individual cytoskeletal structure. This is achieved by regenerating a numerical cytoskeleton based on microscope images of the actin network of each cell. The resulting numerical structure consequently represents pulling characteristics on its environment similar to those generated by the cell in-vivo . From actin imaging we can calculate and better understand how forces are transmitted throughout the cell.